PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAIPADA SEKRETARIAT DAERAHKABUPATEN LOMBOK TENGAH - Mastur Mastur; zainal abidin; Alamsyah Alamsyah (Master of Management, Mataram University, 2015)
This study was conducted to determine the effect of organizational culture and effectiveness ofleadership style to motivate employees to work at the Regional Secretariat of Central Lombok Regency. The problem of motivation is a topic that never ceases to be extracted in order to achieve an understanding of the theoretical with the practical ability in everyday life, especially motivating employees in government agencies.This research is an associative causal, with 137 respondents. Samples determined usingsampling random sampling technique. Data collection toolwas questionnaire with Likert scale. Data were analyzed by using multiple linear regressions.The results showed that the effectiveness of the organizational culture and leadership style has a significant and positive effect on the motivation of employees either partially or simultaneously.Leadership style wasfound as a dominant influencing factor in this research. This study found that organizational culture conducive and positive increase employee motivation to work on, as well as effective leadership will further enhance the work motivation. Harmony and atmosphere that makes employees feel comfortable in working and caring leaders to listen to their employees should be improved so that the employee work motivation will automatically increase.Keywords: Organizational Culture, Leadership Style and Effectiveness of WorkMotivation.